TikTok Reading Challenge Videos in EFL Speaking Practice - Muh. Ridho Pangestu (Journal of English Development, 2026)
This qualitative descriptive study explores EFL students’ perceptions of using TikTok “Reading Challenge” videos as a medium for speaking practice. Although previous studies have examined TikTok as a platform for speaking activities and learner motivation, limited attention has been given to multimodal tasks that integrate reading and speaking fluency in real time. To address this gap, the present study focuses on students’ experiences with Reading Challenge videos that require reading aloud rapidly changing on-screen text. Five English Education students from Tadulako University who had independently engaged in the Reading Challenge participated in the study. Data were collected through semi-structured interviews and analyzed thematically. The findings indicate that the Reading Challenge promotes spontaneous engagement and motivation by providing an enjoyable and less formal space for speaking practice. It also supports the development of pronunciation and fluency through focused attention on timing, articulation, and rhythm. In addition, opportunities for repeated practice in a private setting help reduce speaking anxiety and build confidence. However, participants also reported challenges related to maintaining accuracy and comprehension when following fast-moving text. Overall, this study contributes to existing research by highlighting TikTok Reading Challenge videos as a self-directed multimodal practice that bridges reading and speaking skills within Mobile-Assisted Language Learning (MALL) contexts